Asia under Western Eyes: A Brief Presentation of a Projected Article - Lim, Chee Seng (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Since this is very brief presentation today, I will avoid the well-beaten track of postcolonial discourse after Edward Said’s Orientalism and go back to the beginnings of the imperial era in the early modern period which has only come to a close in Asia at the very end of the twentieth century in Macao. Every schoolboy of my generation knows about Rudyard Kipling’s statement on the distinctiveness of the East, and the West in his “Ballad of East and West”: Oh, the East is East and the West is West, and never the twain shall meet, Till earth and sky stand presently at God’s great judgment seat. This view of things hopes for a meeting and reconciliation at the end of human history before God’s great judgment seat. I am more interested in the possibility of East and West meeting in the here and now.